2017
DOI: 10.1002/ptr.5839
|View full text |Cite
|
Sign up to set email alerts
|

StandardizedPassiflora incarnataL. Extract Reverts the Analgesia Induced by Alcohol Withdrawal in Rats

Abstract: Passiflora incarnata L. (Passifloraceae) has been traditionally used for treatment of anxiety, insomnia, drug addiction, mild infections, and pain. The aim of this study was to investigate the effect of a commercial extract of P. incarnata in the analgesia induced by alcohol withdrawal syndrome in rats. In addition, brain-derived neurotrophic factor and interleukin-10 levels were evaluated in prefrontal cortex, brainstem, and hippocampus. Male adult rats received by oral gavage: (1: water group) water for 19 d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 69 publications
0
8
0
Order By: Relevance
“…The edible parts are considered to be nutraceutical/functional food [39]. The aerial parts of Passiflora plants are used as infusions, extracts, or tinctures due to their various effects: anti-depressive/anti-anxiolytic [40,41]; sedative/anti-sleep disorders [42]; anti-spasmolytic [43]; anti-asthma/anti-respiratory disorders [44]; anti-diabetic/hypolipidemic [45]; anti-hypertensive [46]; and, anti-addictive [47,48]. These effects have been related to the bioactive polyphenols and flavonoids [49,50] and their antioxidant [51][52][53], antimicrobial [52], prebiotic [51], and anti-inflammatory and analgesic [54][55][56] activities.…”
Section: Introductionmentioning
confidence: 99%
“…The edible parts are considered to be nutraceutical/functional food [39]. The aerial parts of Passiflora plants are used as infusions, extracts, or tinctures due to their various effects: anti-depressive/anti-anxiolytic [40,41]; sedative/anti-sleep disorders [42]; anti-spasmolytic [43]; anti-asthma/anti-respiratory disorders [44]; anti-diabetic/hypolipidemic [45]; anti-hypertensive [46]; and, anti-addictive [47,48]. These effects have been related to the bioactive polyphenols and flavonoids [49,50] and their antioxidant [51][52][53], antimicrobial [52], prebiotic [51], and anti-inflammatory and analgesic [54][55][56] activities.…”
Section: Introductionmentioning
confidence: 99%
“…It has sedative and anxiolytic properties (Dhawan, Kumar & Sharma, 2001;Carlini, 2003;Miroddi et al, 2013;da Cunha et al, 2021). It has been used to treat anxiety, insomnia, drug dependence, mild infections, and pain (Schunck et al, 2017). Additionaly, it can be used to control anxiety caused by dental procedures (Kaviani et al, 2013;da Cunha et al, 2021).…”
Section: Passiflora (Passiflora Incarnata)mentioning
confidence: 99%
“…Passiflora incarnata L. (Passifloraceae) is used in traditional herbal medicines, which has shown different therapeutic properties 16,17 . Interestingly, in India, it is used to treat morphine's dependence 18, while in Africa, it is used for its sedative and analgesic properties 19,20 . The P. incarnata is not narcotic or addictive, so it is used in tea, pills, and drops for treatment of sleep disorders, restlessness, irritability, and anxiety 15,21,22 .…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, many studies have been conducted on the effective substances of this plant as anti-anxiety and toxicity properties [23][24][25] , and as a benzodiazepinereceptor agonist 24 . Animal studies have also revealed that P. incarnata L. has been effective in controlling the pain caused by alcohol withdrawal 20 . Meanwhile, other studies have indicated that when the plant is used in the treatment, it reduces the need for opioids in addicts 26 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation